Reflecting on Kejawen: Javanese Esoteric Teachings in Indonesian National Development - Wasisto, Muhammad Adiz (Udayana Journal of Law and Culture, 2021)
Kejawen as a concept of spirituality arose out of ancient Javanese society. Many Western scholars have used the term ‘Javanese mysticism’ to refer to Kejawen teachings, which focus on inward rather than outward religious expression and feeling. Kejawen teaching offers an esoteric understanding of religion and spirituality, one that seems to circulate mainly outside formal religious traditions. This paper demonstrates the significance of Kejawen teaching in spiritual, psychological, and social development in Indonesia, suggesting it has especial relevance to issues of peace and violence. Placing Kejawen in its context, this study shows that the national development in Indonesia after independence was influenced by the esoteric ideas of Kejawen, as portrayed in the national motto “unity in diversity”. This expression resembles the post-independence state ideology of Pancasila.  Through analysis of key nationalist texts, themes linked to elements of Kejawen teachings are identified and analysed in this study. This is done by analysing key texts, including Soekarno’s independence speech, Pancasila, and other relevant materials from various available sources. The reader will find out more about the need for comprehensive symbolic and resource-based recognition of Kejawen teachings in Indonesian society.